A composite scaffold fabricated with an acellular matrix and biodegradable polyurethane for the in vivo regeneration of pig bile duct defects. (15th September 2022) - Jiang, Xia; Xiong, Xianze; Lin, Yixin; Lu, Yanrong; Cheng, Jingqiu; Cheng, Nansheng; Zhang, Jie
Abstract: Bile duct regeneration is urgently needed to restore the normal function of the damaged biliary system. In this study, an artificial bile duct (ABD) was fabricated for extrahepatic bile duct regeneration based on biodegradable polyurethane (BPU) and ureter acellular matrix (UAM) to endow it with favorable biocompatibility and eliminate bile leakage during in vivo bile duct regeneration. The mechanical properties, in vitro simulation of bile flow and cytocompatibility of BPU-UAM ABD were evaluated in vitro, and surgical implantation in the biliary defect site in minipigs was implemented to reveal the in vivo degradation of BPU-UAM and regeneration of the new bile duct. The results indicated that BPU-UAM ABD with a mechanical strength of 11.9 MPa has excellent cytocompatibility to support 3T3 fibroblast survival and proliferation in extraction medium and on the scaffolds. The in vivo implantation of BPU-UAM ABD revealed the change of collagen content throughout the new bile duct regeneration. Biliary epithelial cells were observed at day 70, and continuous biliary epithelial layer formation was observed after 100 days of implantation. Altogether, the BPU-UAM ABD fabricated in this study possesses excellent properties for application study in the regeneration of bile duct. Statement of significance: Extrahepatic bile duct defects carry considerable morbidity and mortality because they are the only pathway for bile to go down into the intestinal tract. At present, no artificial bile duct can promote biliary regeneration. In this study, BPU-UAM ABD was built based on biodegradable polyurethane and ureter acellular matrix to form a continuous compact layer of polyurethane in the internal wall of UAM and avoid bile leakage and experimental failure during in vivo implantation. Our work verified the effectiveness of the synthesized biodegradable polyurethane emulsion-modified urethral acellular matrix in bile regeneration and continuous biliary epithelial layer formation. This study provided a new approach for the curing of bile duct defects and inducing new bile tissue formation. Graphical abstract: Image, graphical abstract